Unraveling the connection between vegetation greening and terrestrial water storage decline in the arid and semi-arid regions of northwest China - Jiaxi Tian; Hao Wang; Zengxin Zhang; Yuanhai Fu; Tianbao Zhao; Hui Tao (Journal of Hydrology: Regional Studies, 2023)
Study Region: Arid and semi-arid regions of Northwest China (NWC) Study Focus: Water scarcity poses a significant challenge to the development of NWC. Although the climate is getting warmer and wetter in NWC, there is a clear intensification in the trend of regional hydrological aridification. However, the connection between these factors continues to remain elusive to our comprehension. This study investigated the impacts of vegetation changes on terrestrial water storage (TWS) and explored their underlying causes using the Lund-Potsdam-Jena (LPJ) Dynamic Global Vegetation Model based on long-term hydrometeorological data, TWS anomaly data, and Normalized Difference Vegetation Index (NDVI) data. New Hydrological Insights for the Region: This study unveils a significant upsurge in NDVI and actual evaporation (E) within NWC during 1982–2019, with distinct prominence observed in cultivated regions. This heightened E emerges as a central driver behind the reduction in surface soil water, root zone soil water, and the continuous decline of TWS across the NWC. The research discerns the amplified E, influenced by both climatic and human activities, as a key contributor to the diminution of TWS within the region. Notably, the contribution of cultivated land E exhibits consistent expansion, while grassland E remains pivotal in TWS reduction. Transpiration (Et) and bare-soil evaporation (Eb) surface as the predominant elements of terrestrial E. The degradation of grasslands leads to intensified Eb, thereby further augmenting E.